The celebrated treatise of Joach. Fortius Ringelbergius De ratione studii - Van Ringelbergh, Joachim Sterck, 1499-1531.; Earp, George Butler (London : Simpkin & Marshall, 1830)
The appendix compromises the Latin original of the chapters omitted in the translation.
Also available in digital form on the Internet Archive Web site.
Keywords: Learning and scholarship